Electronic Textile from Lyocell and Very Few Layer Graphene: Studies and Review - Aminati, Ikha Setya; Amri, Amun; Amri, Evelyn (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2022)
Electronic textiles (e-textiles) are generally made by coating fabrics with conductive particles to impart conductive and electromagnetic properties to textile fibers and filaments. E-textile can be made by several methods, such as "dip and dry", pad-dry, screen-printing, or injeksi printing. Lyocell is the latest generation of cellulose fibers that are used as textile raw materials. Lyocell has naturally hyperhydrophilic properties and greater moisture absorption. Then, graphene is a nanomaterial composed of carbon atoms with a hexagonal structure, it has a very high conductivity value, reaching 104 S/cm. Graphene can be produced in several forms, such as very few layer graphene (VFLG). This paper aims to improve understanding of the research and review of electronic textiles created by combining lyocell textile with very few layer graphene (VFLG). This composition can enable the formation of sustainable electronic textile composites.